Internal tides drive spatial variation in impact areas of deep-sea mining plumes at seamounts - Saito, Naoki; Washburn, Travis W.; Nagao, Masayuki; Kamoshida, Hiroko; Suzuki, Atsushi (Frontiers in Marine Science, 2025)
Deep-sea mining at seamounts can generate large amounts of suspended particles, or sediment plumes, which have the potential to cause environmental impacts. The physical oceanography at seamounts, including internal tides, is expected to complicate plume behavior. However, research incorporating numerical simulations to evaluate this influence is virtually nonexistent. In this study, we conducted hydrodynamic modeling and simulated dispersal and deposition of plumes across the entire seamount summit. The simulations were based on a crust excavation test conducted in 2020 and targeted suspended particles of ≥30 μm, which accounted for the majority of the plume volume. The modeled near-bottom tidal currents at the summit were ≤7 times stronger than those outside the seamount, indicating the occurrence of internal tides, with tidal current strength varying spatially across the summit. The deposition distances of plumes varied by a factor of ≤6.5 ( 120–800 m), depending on the discharge location. Plumes tended to be deposited farther and in a thinner layer around sites with stronger tidal currents, whereas they were deposited closer and thicker around sites with weaker tidal currents. This study suggests that the spatial variability in tidal current strength, driven by internal tides, can alter the extent of plume dispersal and deposition by several-fold depending on the mining site. Understanding oceanographic heterogeneity within seamount summits can be crucial for assessing and mitigating the environmental impacts of mining.